2023
DOI: 10.1080/21645515.2023.2207442
|View full text |Cite
|
Sign up to set email alerts
|

Intention to receive COVID-19 vaccine and its health belief model (HBM)-based predictors: A systematic review and meta-analysis

Abstract: The purpose of the research was to pool the intention to receive the COVID-19 vaccine and its health belief model (HBM)-based predictors, which is helpful for decision-makers and program managers around the globe. The relevant database was searched and Joanna Briggs Institute (JBI) appraisal checklist was used to evaluate the studies. I2 test and funnel plot was utilized to check heterogeneity and publication bias, respectively. DerSimonian and Laird random-effects model was used. The overall pooled intention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This is consistent with our study that showed that participants with low perceived booster vaccination benefits were associated with booster refusal. Similar to our study, Yenew and colleagues also found that greater perceived vaccination barriers were associated with booster refusal [ 21 ]. Another study evaluating the intention of parents to vaccinate their children showed that unwillingness to vaccinate was associated with greater parental perception of barriers and lower benefits [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with our study that showed that participants with low perceived booster vaccination benefits were associated with booster refusal. Similar to our study, Yenew and colleagues also found that greater perceived vaccination barriers were associated with booster refusal [ 21 ]. Another study evaluating the intention of parents to vaccinate their children showed that unwillingness to vaccinate was associated with greater parental perception of barriers and lower benefits [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…The study determined that perceived susceptibility and self-efficacy were significant influencing factors, echoing findings from earlier research. 27 Perceived susceptibility, the degree to which an individual feels at risk of contracting a disease, differs greatly among individuals. 28 Following the revocation of the PHEIC status by the WHO, there has been a public perception that COVID-19 is no longer a threat.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study currently exists examining determinants from both the HBM and COM-B models for COVID-19 vaccination uptake in young adults. Studies examining the HBM (15,(21)(22)(23)(24)(25) and COM-B (26) models in general adult population for COVID-19 vaccination uptake found that higher perceived severity, susceptibility, bene ts, cues to action, capability, opportunity and motivation, and lower perceived barriers predicted greater COVID-19 vaccine uptake.…”
Section: Introductionmentioning
confidence: 99%